2007
DOI: 10.1002/bio.974
|View full text |Cite
|
Sign up to set email alerts
|

In vitro scavenging activity for reactive oxygen species by N‐substituted indole‐2‐carboxylic acid esters

Abstract: The hydroxyl radical (HO*)- and superoxide anion radical (O* (2))-scavenging activity, as well as the singlet oxygen ((1)O(2))-quenching property of N-substituted indole-2-carboxylic acid esters (INDs) were investigated by deoxyribose degradation assay, a chemiluminescence method and the electron spin resonance (ESR) spin-trapping technique. This novel group of compounds was developed as a search for cyclooxygenase-2 (COX-2)-selective enzyme inhibitors. The results obtained demonstrated that of the 16 compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Furthermore TRA, as others indolic compounds are very efficient antioxidants, protecting both lipids and proteins from peroxidation, and it is known that the indole structure influences their antioxidant efficacy in biological systems [1][2][3][4]. Radical scavenging by indolic compounds is strongly modulated by their functional residues.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore TRA, as others indolic compounds are very efficient antioxidants, protecting both lipids and proteins from peroxidation, and it is known that the indole structure influences their antioxidant efficacy in biological systems [1][2][3][4]. Radical scavenging by indolic compounds is strongly modulated by their functional residues.…”
Section: Introductionmentioning
confidence: 99%
“…For the m-THPC (5,10,15,20-tetra(m-hydroxyphenyl)chlorin) sensitizer, the singlet oxygen lifetime in DMSO is 19 ls compared to 65 ls in CH 3 CN [97]. According to the literature, DMSO, H 2 O, CH 3 OH, C 2 H 5 OH and DMF are singlet oxygen quenchers [98][99][100]. In addition, it is confirmed that the lifetime of 1 O 2 in acetonitrile is high.…”
Section: Resultsmentioning
confidence: 80%
“…Recently, we developed a series of novel coxibs based on a 2,3-diarylsubstituted indole chemical lead with high affinity and selectivity for COX-2 as important templates for radiotracer design [33,37]. Obviously, the dual benefit of indole scaffolds providing both a COX-2 pharmacophore and an antioxidant pharmacophore is of particular interest to us and others [34,37,51]. In this regard, the novel 2,3-diaryl-indole coxibs were shown to substantially decrease the formation of lipid and protein oxidation products in a low density lipoprotein oxidation model [37].…”
Section: Introductionmentioning
confidence: 99%